Comparative tissue pharmacokinetics and efficacy of moxidectin, abamectin and ivermectin in lambs infected with resistant nematodes: Impact of drug treatments on parasite P-glycoprotein expression - Lloberas, María Mercedes (2013)
The high level of resistance to the macrocyclic lactones has encouraged the search for strategies to optimize their potential as antiparasitic agents. There is a need for pharmaco-parasitological studies addressing the kinetic-dynamic differences between various macrocyclic lactones under standardized in vivo conditions. The current work evaluated the relationship among systemic drug exposure, target tissue availabilities and the pattern of drug accumulation within resistant Haemonchus contortus for moxidectin, abamectin and ivermectin. Drug concentrations in plasma, target tissues and parasites were measured by high performance liquid chromatography. Additionally, the efficacy of the three molecules was evaluated in lambs infected with resistant nematodes by classical parasitological methods. Furthermore, the comparative determination of the level of expression of P-glycoprotein (P-gp2) in H. contortus recovered from lambs treated with each drug was performed by real time PCR. A longer persistence of moxidectin (P < 0.05) concentrations in plasma was observed. The concentrations of the three compounds in the mucosal tissue and digestive contents were significant higher than those measured in plasma. Drug concentrations were in a range between 452 ng/g (0.5 day post-treatment) and 32 ng/g (2 days post-treatment) in the gastrointestinal (GI) contents (abomasal and intestinal). Concentrations of the three compounds in H. contortus were in a similar range to those observed in the abomasal contents (positive correlation P = 0.0002). Lower moxidectin concentrations were recovered within adult H. contortus compared to abamectin and ivermectin at day 2 post-treatment. However, the efficacy against H. contortus was 20.1% (ivermectin), 39.7% (abamectin) and 89.6% (moxidectin). Only the ivermectin treatment induced an enhancement on the expression of P-gp2 in the recovered adult H. contortus, reaching higher values at 12 and 24 h post-administration compared to control (untreated) worms. This comparative pharmacological evaluation of three of the most used macrocyclic lactones compounds provides new insights into the action of these drugs.